2010
DOI: 10.1142/s1758825110000603
|View full text |Cite
|
Sign up to set email alerts
|

Les and "In Vitro" Experimental Validation of Flow Around a Teeth-Shaped Obstacle

Abstract: The current paper aims to provide numerical and experimental flow data relevant for physical modelling of human fricative sound production due to the interaction of airflow with the teeth. A simplified upper incisor-palate geometry is derived from typical morphological features. The geometry is inserted in a rectangular channel for which the width-to-height ratio yields 4. The obstruction degree due to the presence of the simplified upper incisor yields 70%. Numerical flow data are obtained from large eddy sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…A few common examples are obstructive sleep apnea (5% of adult population), vocal folds polyps (common among e.g. teachers due to intensive professional voice use), cancer of the tongue/larynx requiring (a) incisor and free field [4] (b) tongue-incisor [23], [5] (c) tongue-incisor [22] (d) human [12] surgical interventions or common interventions at the teeth. Consequently, accurate upper airway flow modeling contributes to the development of tools aiming to improve basic health care and daily life comfort with respect to e.g.…”
Section: A Real-life Application: Human Upper Airway Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…A few common examples are obstructive sleep apnea (5% of adult population), vocal folds polyps (common among e.g. teachers due to intensive professional voice use), cancer of the tongue/larynx requiring (a) incisor and free field [4] (b) tongue-incisor [23], [5] (c) tongue-incisor [22] (d) human [12] surgical interventions or common interventions at the teeth. Consequently, accurate upper airway flow modeling contributes to the development of tools aiming to improve basic health care and daily life comfort with respect to e.g.…”
Section: A Real-life Application: Human Upper Airway Flowmentioning
confidence: 99%
“…2 as function of geometrical parameters is performed [22], [4], [5], [21], [3]. The flow domain consists of an oral tract geometry extended with an outlet cavity ( Fig.…”
Section: B Flow and Acoustic Simulated Datamentioning
confidence: 99%
“…In fact, LES offers more accurate results over other turbulent models such as the Reynolds-averaged Navier-Stokes equation for flows involving flow separation and acoustic prediction, which requires unsteady vorticity field [9]. Van Hirtum et al [10] gathered velocity information in a flow provoked by the impingement of a laminar jet onto a tooth-shaped obstacle by implementing LES. Ramsay and Shadle [11] similarly revealed the geometric effects of constriction on the initiation of a vorticity structure in a glottal jet that developed in the vocal tract during the production of fricatives.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Borden et al [13] reported a flow rate of 500 mL/s, and Stevens [14] set it at 250-700 mL/s. Based on these estimates, the Reynolds numbers in previous simulation studies were set at around 4000-5000 [10,11]. However, individual variations in the flow rate to produce sibilant /s/ would be significantly larger if we took into account the individual variations in the size of the oral cavity [15] and the level of sound intonation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a simplified vocal tract/teeth obstacle allows focusing the study on one particular phenomenon which can be isolated. Moreover, it allows carrying out in-vitro experiments using the same geometry [13] which can be compared to results obtained from numerical simulations in order to provide an experimental validation of the physical modeling [14].…”
mentioning
confidence: 99%